Symbolic Capital and Tourism Propulsion of Talad Noi Community, Bangkok - Ruangjan, Por Prapassanan; Preededilok, Fuangarun; Yuenyong, Phathara (Journal of Cultural Approach, 2023)
Symbolic capital is one of the most powerful capitals in society. It gives meaning to other types of capital that affect people’s perceptions of society and ultimately causes changes in society. Likewise, the revival of an old community that has been forgotten can lead to a lively, valuable, and economically viable area like Talad Noi. The 200 years old community in Bangkok, was restored to conduct economic activities through tourism. Therefore, this article aims to explain the use of symbolic capital in driving tourism in the Talad Noi community. Symbolic capital, an important driving force that generates and continues the tourism of Talad Noi community, is caused by changing the perception of both insiders and outsiders of the community towards the cultural capital that the community has. The perception has been transformed into a modern perception that can be accepted by a wider range of people. Essentially, such a changed perception of people creates symbolic capital for the community. More importantly, it potentially draws attention from the government and private sectors that drive strategic communication and public relations, which are important activities in creating and maintaining symbolic capital.